2016
DOI: 10.3390/brainsci6030039
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into Deep Brain Stimulation Lead Designs: A Patient-Specific Simulation Study

Abstract: New deep brain stimulation (DBS) electrode designs offer operation in voltage and current mode and capability to steer the electric field (EF). The aim of the study was to compare the EF distributions of four DBS leads at equivalent amplitudes (3 V and 3.4 mA). Finite element method (FEM) simulations (n = 38) around cylindrical contacts (leads 3389, 6148) or equivalent contact configurations (leads 6180, SureStim1) were performed using homogeneous and patient-specific (heterogeneous) brain tissue models. Steer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 30 publications
4
68
0
Order By: Relevance
“…The solvers were set to stop when the calculated distance difference fell below 0.01 mm. The activation distances for the 5.7 µm axon for Model I was 3.2 mm ( Figure 35), and for Model II was 2.6 mm ( Figure 34) which is in line with the distances previously published [6,10,60,67,75].…”
Section: Neuron Model Evaluationssupporting
confidence: 89%
“…The solvers were set to stop when the calculated distance difference fell below 0.01 mm. The activation distances for the 5.7 µm axon for Model I was 3.2 mm ( Figure 35), and for Model II was 2.6 mm ( Figure 34) which is in line with the distances previously published [6,10,60,67,75].…”
Section: Neuron Model Evaluationssupporting
confidence: 89%
“…Field threshold values determined with this approach are used in several computational studies to estimate the neural activation extent during DBS [25], [26], [27]. The determined normalized activation thresholds determined in this study with growth factors between 29 % to 35 % for a 5.7 µm and 47 % to 74 % for a 2.0 µm axon suggest that this approach leads to an over-and underestimation of the neural activation extent with volume deviations of up to 24 % by using a constant electric field norm threshold for all stimulation amplitudes (Table II).…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus of the degree of complexity of the model to accurately simulate the neural response, however, many groups (Chaturvedi et al, 2010; Schmidt et al, 2013; Alonso et al, 2016; Howell and McIntyre, 2016) have shown that the inclusion of the heterogeneity and anisotropy of the brain tissue increases the model accuracy and prediction capability. For instance, Chaturvedi et al (2010) and Åström et al (2012) observed an overestimation of neural activation for homogeneous models.…”
Section: Discussionmentioning
confidence: 99%
“…In a next step, it was imported into the in-house developed software (Matlab R2013) (Wårdell et al, 2012) modified for the creation of the brain tissue models. A separate filtered axial T1 image batch with enhanced region of interest was used to segment cerebrospinal fluid (CSF), gray matter and white matter (Alonso et al, 2016). The segmented image voxels were assigned with the corresponding electrical conductivities (σ) (Gabriel et al, 1996) 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation